2023
DOI: 10.21203/rs.3.rs-2718787/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The weakening AMOC under extreme climate change

Abstract: We examine changes in the Atlantic Meridional Overturning Circulation (AMOC) in the quadrupled CO2 experiments conducted under the sixth Coupled Model Intercomparison Project (CMIP6). The increase in CO2 triggers extensive Arctic warming, causing widespread melting of sea ice. The resulting freshwater spreads southward, first from the Labrador Sea and then the Nordic Seas, and proceeds southward along the eastern coast of North America. The freshwater enters the subpolar gyre north of the separated Gulf Strea… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 86 publications
0
1
0
Order By: Relevance
“…Gregory et al (2016) found that for forcings derived from doubling CO2 gradually over 70 years (1pctCO2), only heat flux changes lead to significant AMOC weakening, whereas freshwater flux other than ice sheet runoff has no significant impact. However, a recent preprint (Madan et al , 2023) suggests that for instantaneous CO2 quadrupling in CMIP6, freshwater forcing from sea ice melt weakens AMOC. Liu, Fedorov and Sévellec (2019) also suggested that changes in sea ice cover may impact AMOC through changes in freshwater input (freezing, advection and melting of ice floes) and heat flux (e.g., shielding ocean water from atmospheric influences).…”
Section: Drivers and Feedbacksmentioning
confidence: 99%
“…Gregory et al (2016) found that for forcings derived from doubling CO2 gradually over 70 years (1pctCO2), only heat flux changes lead to significant AMOC weakening, whereas freshwater flux other than ice sheet runoff has no significant impact. However, a recent preprint (Madan et al , 2023) suggests that for instantaneous CO2 quadrupling in CMIP6, freshwater forcing from sea ice melt weakens AMOC. Liu, Fedorov and Sévellec (2019) also suggested that changes in sea ice cover may impact AMOC through changes in freshwater input (freezing, advection and melting of ice floes) and heat flux (e.g., shielding ocean water from atmospheric influences).…”
Section: Drivers and Feedbacksmentioning
confidence: 99%